2020
DOI: 10.3389/fpsyt.2020.00701
|View full text |Cite
|
Sign up to set email alerts
|

Instructed Partnership Appreciation in Depression: Effects on Mood, Momentary Relationship Satisfaction, and Psychobiological Arousal

Abstract: Background: Depressive disorders are associated with attentional bias and social anhedonia. There is evidence supporting the hypothesis that depressed individuals participate less in potentially rewarding social situations and exhibit alterations in stress reactivity. With the present study, we aimed at investigating the affective and psychobiological response of couples with a depressed (female) partner in an instructed partnership appreciation task (PAT) that included positive and appreciative communication.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 101 publications
(141 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, the sample consisted of healthy young couples reporting high relationship satisfaction only. Given inconsistent effects of instructed partnership appreciation in clinical samples (Warth et al, 2020) or couples in therapy (Aguilar-Raab et al, 2018), we cannot extrapolate our findings to marital problems or patient populations (see for instance a study in couple with substance abuse by Flanagan et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the sample consisted of healthy young couples reporting high relationship satisfaction only. Given inconsistent effects of instructed partnership appreciation in clinical samples (Warth et al, 2020) or couples in therapy (Aguilar-Raab et al, 2018), we cannot extrapolate our findings to marital problems or patient populations (see for instance a study in couple with substance abuse by Flanagan et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…Based on this, receiving compliments from the partner can be considered highly relevant to evaluating the social self, the level of integration and affection and, thereby, act in a particularly rewarding and health-beneficial way. To investigate the neural responses to tender partner compliments, we have adapted the previously established standard instructed partnership appreciation task (Pfeifer et al, 2020; Warth et al, 2020) for a functional imaging (fMRI) paradigm. We compared compliments from the partner to “self compliments” (i.e., attributes that the participants defined about themselves), since the mental reflection of positive attributes per se could improve mood (Nicolson et al, 2020) by activating reward-related brain areas (Izuma et al, 2008; Frewen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We used a 2 × 2 design. Couples were randomized into OT group versus placebo group, and a condition in which one group was instructed to engage in a short verbal partnership appreciation task (PAT) (41) which they should implement in their everyday lives during the assessment period and a group without such instructions (NPAT). This intervention, conceptualized as appreciation of the relationship and positive personal characteristics of each partner (40), was supposed to lead the focus on highly individual and positive relationship aspects, thereby increasing relationship satisfaction and decreasing stress reactivity.…”
Section: Methodsmentioning
confidence: 99%
“…A meta‐analysis has revealed the effect of relationship quality on psychopathology to be stronger than vice versa, emphasizing the preventive role of healthy relationships (Bodenmann & Randall, 2013). Positive couple interactions have been found to impact biological markers of stress and arousal, which in turn may mediate physical health (Warth et al, 2020). In support of these results, couple therapy has been shown to effectively strengthen emotion regulation and relationship quality in distressed couples and in couples with individual psychopathology (Fischer et al, 2016; Fishbane, 2011; Roesler, 2020).…”
Section: The Impact Of Social Relationships On Healthmentioning
confidence: 99%
“…Empirical findings have provided support for an association between relationship quality and the emergence of mental disorders (Robles et al, 2014). For instance, a recent study has shown that couples with depression report lower relationship quality and are less likely to receive social support from their partner compared with nondepressed couples (Warth et al, 2020). A meta-analysis has revealed the effect of relationship quality on psychopathology to be stronger than vice versa, emphasizing the preventive role of healthy relationships (Bodenmann & Randall, 2013).…”
Section: The Impact Of Social Relationships On Healthmentioning
confidence: 99%